Pengaruh Kecepatan dan Waktu Sentrifugasi terhadap Nilai Hematokrit Mahasiswa AAK Manggala Yogyakarta - Jeniwati Tamo Inya; Pratiwi Ratih Halimatus Sya'diah; Ardina Nugrahani (Jurnal Syntax Admiration, 2024)
A hematocrit test is an examination that aims to diagnose a disease related to the number of red blood cells (erythrocytes). In the laboratory, there are often errors in hematocrit examinations, namely with the inaccuracy of the centrifuge time, with the large number of patients it is one of the obstacles for laboratory staff in conducting examinations, so that the centrifuge is turned off faster and sometimes also late. The purpose of this study is to determine the effect of centrifugation speed and time on hematocrit levels of students in the fourth semester of AAK Manggala Yogyakarta in 2023. This research method is descriptive analytical. The sample of this study is 39 samples. This study uses the microhematocrit method at 15,000 rpm, 12,000 rpm, 10,000 rpm, 7,000 rpm for 5 and 10 minutes with data analysis using the Kruskal Wallis test. The results showed that the average hematocrit value in men was 40% and women was 40%. The results of the statistical test show the significance value 15,000 rpm for 5 and 10 minutes is p=0.631 (p>0.05), 12,000 rpm during 5 and 10 minutes is p= 0.255 (p>0.05), 10,000 rpm for 5 and 10 minutes is p= 0.496 (p>0.05) at 7,000 rpm for 5 and 10 minutes is p=0.316 (p>0.05). The conclusion of this study is that there is no effect of speed and time of snetrifugation on hematocrit values. (p> 0.05).